Emerging prospects of mRNA cancer vaccines: mechanisms, formulations, and challenges in cancer immunotherapy - Umm E. Laila; Wang An; Zhi-Xiang Xu (Frontiers in Immunology)
Cancer continues to pose an alarming threat to global health, necessitating the need for the development of efficient therapeutic solutions despite massive advances in the treatment. mRNA cancer vaccines have emerged as a hopeful avenue, propelled by the victory of mRNA technology in COVID-19 vaccines. The article delves into the intricate mechanisms and formulations of cancer vaccines, highlighting the ongoing efforts to strengthen mRNA stability and ensure successful translation inside target cells. Moreover, it discusses the design and mechanism of action of mRNA, showcasing its potential as a useful benchmark for developing efficacious cancer vaccines. The significance of mRNA therapy and selecting appropriate tumor antigens for the personalized development of mRNA vaccines are emphasized, providing insights into the immune mechanism. Additionally, the review explores the integration of mRNA vaccines with other immunotherapies and the utilization of progressive delivery platforms, such as lipid nanoparticles, to improve immune responses and address challenges related to immune evasion and tumor heterogeneity. While underscoring the advantages of mRNA vaccines, the review also addresses the challenges associated with the susceptibility of RNA to degradation and the difficulty in identifying optimum tumor-specific antigens, along with the potential solutions. Furthermore, it provides a comprehensive overview of the ongoing research efforts aimed at addressing these hurdles and enhancing the effectiveness of mRNA-based cancer vaccines. Overall, this review is a focused and inclusive impression of the present state of mRNA cancer vaccines, outlining their possibilities, challenges, and future predictions in the fight against cancer, ultimately aiding in the development of more targeted therapies against cancer.